(untitled) (مجلة إحالات, 2026)
Arabic literature and critic knew new theories that aimed to replace the classic old critics, the beginning was from western modern theories that relay on science in analyses; an one from thos new modern theories that came from Europ is the narativ semiotic.The narrative semiotic capacitate critics to exanimate different text using precedure that reveal many aspects in the narration , and one of the critics ho process narrative semiotic the Algerian critic "Rashid bin Malik, this study tries to shed light on an important aspect of the semiotic critical experience of critic "Rashid bin Malik", by tracking and monitoring his semiotic approach in his analysis of the narrative texts.